Spectroscopic properties of lithium borate glass containing Sm3+ and Nd3+ ions - I. Kashif; A. Ratep; S. Ahmed (Institute of Advanced Engineering and Science, 2020)
Lithium borate glass samples mixed with a different concentration of Sm3+ and Nd3+ ions organized by quenching technique. Structural, vibration groups and spectral properties of glass samples investigated using X-ray diffraction, FTIR, UV/Vis/NIR and photoluminescence spectroscopy. The X-ray confirmed the lithium borate glass samples containing Sm3+ and Nd3+ ions in the amorphous state. Luminescence spectra of glass samples excited at 400 nm recorded, here three luminescence bands observed in Visible region, which due to spectra materials (Sm3+, Nd3+). These indicate that these glass samples responsible orange emission and used in the improvement of materials for LED, and optical devices. The functional vibration groups of the glass matrix studied using FTIR spectroscopy.